Rethinking the International Legal Framework Protecting Journalists in War and Conflict (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2023)
Journalists reporting from conflict zones are increasingly at risk of injury or death. Not only are they at risk of becoming a casualty in the crossfire, they are now often directly targeted and killed because of their profession. This paper undertakes an examination of the international legal regime for the protection of frontline media workers in armed conflict, with a view to determining its adequacy or otherwise in protecting journalists operating in such dangerous landscapes. The examination includes a study of the current rules and principles of international humanitarian law, international human rights law, and the proposals provided by the regime and international non-governmental bodies. The legal framework protecting journalists in conflict zones consists predominantly of international humanitarian law, supplemented by international human rights law as well as international criminal law. The main body of law providing protection to journalists consists of the Geneva Conventions and their additional protocols, which are now old. The paper found that the legal framework contains, at least in theory, a significant number of provisions that continue to provide protection for journalists in conflict zones. The paper equally found that the international committee of the Red Cross report and the views of most academic literature reveal that the protection offered by the current legal framework is adequate but that the enforcement of it is lacking. This is considered the predominant reason why journalists reporting on conflicts currently face such significant risks to their safety. It concludes that the inadequacies of the current international legal regimes are unsustainable and that there is a need to holistically rethink the protections presently offered by providing a more robust treaty to distinctly cater for the wellbeing of media workers in the forefront of armed conflict.